Novel Centralized Control Battery Operation, on Microgrids to Supply The Load Priority - Hartono Budi Santoso; Wike Handini; Rudy Setiabudy; Budiyanto Budiyanto (Institut Teknologi Sepuluh Nopember, 2014)
Priority loads, in micro grid is preferred load to always get the power supply. Battery function, in micro grid, in addition, functioning as a storage energy, it also serves as a stabilizer of network, due to intermittent of energy sources, both solar and from wind. As energy storage, battery is intended to supply energy when other sources of energy is not available. So far, the mechanism of battery operation, distributed on each generation, so that when operation standalone, battery capacity is not in optimal level. In this study, proposed, method of centralized control battery operation, which would regulate the use of battery operation, especially to supply the load priority. So that the power supply from the battery to the load priority, it would be optimal in optimal level when other sources are no longer, by utilizing parameters weather and load forecast.